The Effects of the Blending Condition on the Morphology, Crystallinity, and Thermal Stability of Cellulose Microfibers Obtained from Bagasse - Romi Sukmawan; Lestari Hetalesi Saputri; Rochmadi Rochmadi; Heru Santoso Budi Rochardjo (Universitas Gadjah Mada, 2019)
In this study, cellulose microfibers were isolated from bagasse fibers in three stages. Initially, the fibers were treated with 5 wt.% NaOH solution followed by bleaching with 5 wt.% H2O2 in an alkali condition (pH 11) to remove hemicelluloses and lignin. Whole cellulosic fibers were obtained by mechanically separating the fibers using a modified kitchen blender to produce cellulose microfibers. Morphological (Scanning Electron Microscopy (SEM)) and structural analysis of the treated fiber was performed using Fourier Transformed Infrared (FTIR) spectroscopy and X-ray Diffraction (XRD). Morphological characterization identified that the diameter of the fibers varied between 20 nm to 20 µm and the FTIR analysis demonstrated that the treatments resulted in the gradual removal of lignin and hemicelluloses from the fiber. Furthermore, the XRD studies revealed that the combination of the chemical and mechanical treatment is an effective way to increase purity of cellulose (removal of amorphous lignin and hemicellulose) and break down the microfiber into shorter crystalline parts with higher crystallinity (77.25%) than raw bagasse (40.54%). Accordingly, changing the agitation time revealed that the cellulose crystallite size in the sample varied slightly with agitation time by using a blender (3.35 nm). Finally, the higher crystallinity and crystallite size improved the thermal stability of the cellulose microfiber confirming their suitability in the manufacturing biomaterial composites.